Bilateral Extrarenal Inguinal Nephroblastomatosis - A Rare Event - Zahra, Kanwal; Khalid, Ahmareen; Tanwani, Ashok Kumar (International Journal of Pathology, 2018)
Objective: To report an unusual case of extrarenal nephroblastomatosis involving bilateral inguinal regions.Background: Nephroblastomatosis and nephrogenic rests are usually found in neonatal kidneys sub-clinically or associatedwith Wilms tumor. Extrarenal occurrence of this immature renal tissue is reported in literature as an incidental finding seen ininguinal canal, retroperitonium, along with a teratoma and sometimes associated with development of Wilms tumor.Involvement of bilateral inguinal regions is quite unusual and is not yet reported. Proper histological diagnosis is mandatoryto distinguish them from Wilms tumor. After diagnosis a conservative therapeutic approach and regular follow-up is all thatis required in these cases.Case Presentation: A 5 months old female baby presented with bilateral inguinal swellings since birth. Initially FNACwas performed, a diagnosis of small round blue cell tumor was made and excision was advised. On H&E slides of excisedspecimen a diagnosis of bilateral extrarenal nephroblastomatosis was made and a close follow-up was advised.Conclusion: Bilateral extrarenal nephroblastomatosis is a rare event. It has a close association with Wilms tumor.Considering the risk a thorough histological examination with proper diagnosis is required to plan appropriate treatmentoptions for the patient. Regular follow-up for early detection of malignant transformation is also mandatory.